2022
DOI: 10.1111/cpr.13223
|View full text |Cite
|
Sign up to set email alerts
|

Human ESC‐derived immunity‐ and matrix‐ regulatory cells ameliorated white matter damage and vascular cognitive impairment in rats subjected to chronic cerebral hypoperfusion

Abstract: Objectives: This study investigated the ability of immunity-and matrix-regulatory cells (IMRCs) to improve cognitive function in a rat model of vascular cognitive impairment. Materials and Methods:A chronic cerebral hypoperfusion (CCH) model was established in rats via permanent bilateral occlusion of the common carotid arteries (two-vessel occlusion, 2VO). The rats then received intravenous injections of IMRCs or saline. A single injection of different doses of IMRCs (1 Â 10 6 cells/rat, 2 Â 10 6 cells/ rat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…The protective effects of AS-IV were reversed when TFEB was knocked down ( 136 ). The integrity of white matter bundles is vital for motor function recovery after SCI ( 137 ), as well as for neuronal communication and cognitive function improvement ( 138 ). Oligodendrocytes, which wrap around axons, form the basic structure of white matter bundles.…”
Section: Ros In Ferroptosismentioning
confidence: 99%
“…The protective effects of AS-IV were reversed when TFEB was knocked down ( 136 ). The integrity of white matter bundles is vital for motor function recovery after SCI ( 137 ), as well as for neuronal communication and cognitive function improvement ( 138 ). Oligodendrocytes, which wrap around axons, form the basic structure of white matter bundles.…”
Section: Ros In Ferroptosismentioning
confidence: 99%
“…Prior research has demonstrated their potential in immunomodulation and tissue repair. For instance, the injection of IMRCs has the capability to suppress pulmonary inflammation and fibrosis following acute lung injury in vivo, 26 , 28 improve cognitive ability in early-stage AD mice, 29 prevent chronic cerebral hypoperfusion induced white matter injury and cognitive impairment, 30 ameliorate the progression of osteoarthritis, 31 etc. Meanwhile, IMRCs-derived extracellular vesicles and secretomes can attenuate pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%